The golden age of minimally invasive cardiothoracic surgery: current and future perspectives. (May 2011) - Iribarne, Alexander; Easterwood, Rachel; Chan, Edward YH; Yang, Jonathan; Soni, Lori; Russo, Mark J; Smith, Craig R; Argenziano, Michael
Over the past decade, minimally invasive cardiothoracic surgery (MICS) has grown in popularity. This growth has been driven, in part, by a desire to translate many of the observed benefits of minimal access surgery, such as decreased pain and reduced surgical trauma, to the cardiac surgical arena. Initial enthusiasm for MICS was tempered by concerns over reduced surgical exposure in highly complex operations and the potential for prolonged operative times and patient safety. With innovations in perfusion techniques, refinement of transthoracic echocardiography and the development of specialized surgical instruments and robotic technology, cardiac surgery was provided with the necessary tools to progress to less invasive approaches. However, much of the early literature on MICS focused on technical reports or small case series. The safety and feasibility of MICS have been demonstrated, yet questions remain regarding the relative efficacy of MICS over traditional sternotomy approaches. Recently, there has been a growth in the body of published literature on MICS long-term outcomes, with most reports suggesting that major cardiac operations that have traditionally been performed through a median sternotomy can be performed through a variety of minimally invasive approaches with equivalent safety and durability. In this article, we examine the technological advancements that have made MICS possible and provide an update on the major areas of cardiac surgery where MICS has demonstrated the most growth, with consideration of current and future directions.